2009
DOI: 10.1111/j.1365-3059.2008.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual control of avirulence in Leptosphaeria maculans towards a Brassica napus cultivar with ‘sylvestris‐derived’ resistance suggests involvement of two resistance genes

Abstract: Blackleg disease (phoma stem canker) of Brassica napus (canola, oilseed rape) is caused by the fungus Leptosphaeria maculans . In some regions of Australia, resistance in oilseed rape cultivars derived from B. rapa subs . sylvestris (e.g. cv. Surpass 400) became ineffective within three years of commercial release. The genetic control of avirulence in L. maculans towards cv. Surpass 400 is described. When Australian field isolates were screened on this cultivar, three phenotypic classes were observed; virulent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 33 publications
3
80
0
Order By: Relevance
“…Similarly, AvrLm6 was confirmed in 94 isolates, but not in two of the 96 isolates. Since 'Surpass 400' is believed to carry both Rlm1 and LepR3 (Van de Wouw et al, 2008), the presence or absence of AvrLepR3 could be confirmed in only 47 of the 96 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, AvrLm6 was confirmed in 94 isolates, but not in two of the 96 isolates. Since 'Surpass 400' is believed to carry both Rlm1 and LepR3 (Van de Wouw et al, 2008), the presence or absence of AvrLepR3 could be confirmed in only 47 of the 96 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of these R genes have been positioned in the A genome of B. napus or B. rapa ( Rlm1, Rlm2, Rlm3, Rlm4, Rlm7, Rlm9, LepR1, LepR2, LepR3, LepR4 ) or the B genome of B. juncea ( LmJR1, LmJR2 ) via linkage mapping (Delourme et al, 2004; Yu et al, 2005, 2007, 2012; Christianson et al, 2006; Long et al, 2011; Raman et al, 2012a,b; Larkan et al, 2013, 2014, 2016), while two more have been assigned to B genome chromosomes of B. juncea and/or B. nigra ( Rlm6, Rlm10 ) through marker-based assessment of recombinant or chromosome addition lines (Chèvre et al, 1996, 1997; Eber et al, 2011). RlmS , identified in the B. napus variety Surpass 400 (Van De Wouw et al, 2009) likely corresponds to the BlmR2 locus mapped to chromosome A10 (Long et al, 2011; Larkan et al, 2013). The remaining R genes ( Rlm5, Rlm8, Rlm11 , and RlmJ1 ) have yet to be genetically characterized in the host Brassica lines in which they reside.…”
Section: Introductionmentioning
confidence: 99%
“…At least eleven R genes conferring resistance to L. maculans have been identified in Brassicas (Delourme et al 2006;Yu et al 2008;Van de Wouw et al 2009). At least nine corresponding L. maculans Avr genes have been genetically characterised (AvrLm1-AvrLm9) and AvrLm1, AvrLm4, AvrLm6 and AvrLm7 have now been cloned (Gout et al 2006;Fudal et al 2007;Parlange et al 2009).…”
Section: Introductionmentioning
confidence: 99%